Risk of Osteoporotic Fracture and Falls among Rural Residents in Malang: an Observational Study - Pratama, Mirza Zaka; Suryana, Bagus Putu Putra; Putra, Domy; Putri, Rina Kurnia (Clinical and Research Journal in Internal Medicine, 2025)
Background: Osteoporosis is a condition characterized by decreased bone density, which increases the risk of fractures, particularly in untreated osteoporosis and when falls occur. The incidence of falls in individuals with osteoporosis is quite high, with 1.5 million out of 34 million people experiencing it, emphasizing the need for awareness among sufferers to prevent it. Indonesia, the fourth most populous country in the world. Aim: The focus of this study is to determine the relationship between fracture risk (the Percentage Ten-Year Probability of Major Osteoporosis and hip fracture) and falls, in relation to sociodemographic and other risk factors in Malang. Methods: The study was conducted in Malang City using a cross-sectional design. A total of 153 participants were selected using purposive sampling. Results: The results showed a strong correlation between menopause status and gender with the percentage ten-year probability of major osteoporosis(p-value for menopause status: 0.007, p-value for gender: 0.008). There was also a strong relationship between age and the Percentage Ten-Year Probability of Hip Fracture (p-value: <0.001). However, no variable had a strong influence on the risk of falling based on the Ontario Modified Stratify-Sydney Scoring for Adultery (p-values: education: 0.271; age: 0.067; menarche status: 0.996; menopause: 0.724; gender: 0.996; BMI: 0.448; TUG: 0.058). Conclusion: Given the findings that show a heightened risk of fractures in older adults, women, and those experiencing menopause, the Malang government could develop policies aimed at early intervention.